A Simple Experiment to Explore Standing Waves in a Flexible Corrugated Sound Tube - P. Simeao Carvalho (2011)
Sound tubes, pipes, and singing rods are used as musical instruments and as toys to perform amusing experiments. In particular, corrugated tubes present unique characteristics with respect to the sounds they can produce; that is why they have been studied so intensively, both at theoretical and experimental levels.Experimental studies usually involve expensive and sophisticated equipment that is out of reach of school laboratory facilities. In this paper we show how to investigate quantitatively the sounds produced by a flexible sound tube corrugated on the inside by using educational equipment readily available in school laboratories, such as the oscilloscope, the microphone, the anemometer, and the air pump. We show that it is possible for students to study the discontinuous spectrum of sounds produced by a flexible corrugated tube and go even further, computing the speed of sound in air with a simple experimental procedure.